Factors That Shape The Decision to Have a Boarding House at Bu Tin's Boarding House in West Surabaya - Linardo, Wilson (Universitas Ciputra Surabaya, 2022)
The definition of boarding house is a type of rental room that is rented for a certain period oftime in accordance with the room owner’s agreement and the agreed price. High demand for boardinghouse in West Surabaya led to higher boarding house competition. By knowing factors that influenceconsumer’s purchasing decision could help Bu Tin’s boarding house withstand in the competition andincrease occupancy rate. The results obtained are that exploratory factor analysis can be used to determineconsidered factors in determining factors that influence consumer’s purchasing decision. It is based oneigen value of seven factors that has value more than one. The formed factors were insurance, mobility,property design & layout, property facility, service convenience, curfew flexibility, price.